Chemical study of Adenocalymma axillarum crude leaf extract and isolated compounds - João Paulo Campos Andrade; Osvaine Junior Alvarenga Alves; Marian Caroline Costa; Valéria Maria Melleiro Gimenez; Iara Silva Squarisi; Heloiza Diniz Nicolella; Mariana Cintra Pagotti; Denise Crispim Tavares; Wilson Roberto Cunha; Márcio Luís Andrade e Silva; Ana Helena Januario; Lizandra Guidi Magalhães; et al. (Universidade de São Paulo, 2020)
Abstract Adenocalymma axillarum (K.Schum.) L.G. Lohmann is a liana belonging to the family Bignoniaceae. In traditional medicine, the genus Adenocalymma is used to treat fever, skin ailments, and body, joint, and facial muscle pains, and it is also applied as cosmetic. Biological assays conducted with the A. axillarum crude leaf ethanol extract have indicated leishmanicidal activity and absence of cytotoxicity. This study aimed to analyze the A. axillarum leaf ethanol crude extract by high-performance liquid chromatography-high-resolution mass spectrometry- diode array detector (HPLC-HRMS-DAD) and to evaluate the leishmanicidal and cytotoxic activities of this crude extract, its fractions, and isolated compounds. HPLC-HRMS-DAD analysis of this extract revealed that it consisted mainly of flavonoids, with nine major compounds. Extract purification yielded 4-hydroxy-N-methylproline, 6-β-hydroxyipolamiide, quercetin-3-O-robinobioside, hyperin, isorhamnetin-3-O-robinobioside, and 3'-O-methylhyperin, which were identified by Nuclear Magnetic Resonance. The isolated compounds were inactive against Leishmania amazonensis promastigotes and human lung fibroblast cells.